Biochemical Polymorphism in Broiler Rabbits - Usha A P (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 1990)
Blood samples collected from rabbits maintained in the rabbit breeding farm of Kerala Agricultural University formed the materials for this study. These blood samples were typed employing horizontal polyacrylamide gel electrophoresis to study the polymorphism of transferrin, post transferrin and haemoglobin. A total of 152 rabbits comprising of 50 Soviet Chinchilla, 52 Newzealand White and 50 local rabbits were involved in the study. Genetic inter relationship among growth traits and survivability were studied. In all the genetic groups, two transferrin variants, the faster TfA and slower TfC with two phenotypes TfAA and TfAC were observed. The gene frequency of TfA and TfC were 0.7500 and 0.2500 in Soviet Chinchilla, 0.8300 and 0.1700 in Newzealand White and 0.8100 and 0.1900 in local rabbits. The frequency of TfA allele was higher in all the populations. The phenotype TfCC was not observed in any of the genetic groups. Three post transferrin phenotypes Ptf FF, Ptf FS and Ptf SS were detected and found to be controlled by two co – dominant alleles, PtfF and PtfS. The fast moving variant was designated as PtfF and the slow moving migrant was designated as PtfS. The gene frequency of PtfF was 0.7400, 0.8500 and 0.7600 in the three genetic groups and that of PtfS was 0.2600, 0.1500 and 0.2400 in Soviet Chinchilla, Newzealand White and local rabbits respectively. Haemoglobin was found to be monomorphic in all the three genetic groups studied. The allelic frequencies of transferrin and post transferrin were suggestive of Hardy Weinberg equilibrium in the populations of three breeds. No significant diversity was found to exist between genetic groups. Analysis of segretation pattern observed in pedigrees revealed the autosomal codominant mode of inheritance for transferrin and post transferrin alleles. The absence of TfCC phenotype in the whole population of rabbits may be due to its unfavourable influence on the viability. Significant association was observed between the TfAA phenotype and body weight at the ages of 15 days, 30 days, 45 days, 60 days, 75 days and 90 days of age in Soviet Chinchilla and local rabbits. But no significant association was observed between transferrin phenotype and reproductive traits studied. Average daily gain was found to have no significant association with the protein types in any of the genetic groups studied. Preweaning mortality was 38.46 percent in TfAA x TfAA matings and 28.57 percent in TfAC x TfAC matings. Post transferrin phenotype was found to have no significant association with any of the economic traits studied. Among the three biochemical of blood studied, transferrin and post transferrin reflected a great scope for genetic monitoring of populations of rabbits.